Cuuute! Spooks and Vocal Expressions in Speaking to Puppies - Battistini, Emiliano (E|C, 2020)
In this contribution we will focus on a typical form of communication in referring and speaking to puppies, the one that links the use of pet names as "cute" to a particular and specific type of vocalization. We will analyse this communicative behaviour through a series of family videos that show the interaction between human adults and puppies, trying to highlight the semiotic mechanisms that underlie it. Coherent set of small narratives, these videos are part of the daily self branding practices made possible by social media such as YouTube and are interesting for their showing a practice - the greeting to human and animal puppies through the use of nicknames and specific vocal expressions - that finds in the sound dimension the main relevance, showing how, again, the semantic class of "puppies", which refers to the young of each animal species including humans, if properly explored, leads to unexpected convergences of the semantic universes of human and animal.